Circulating respiratory viruses including SARS-CoV-2 during 2021-2022 season in Tunisia: Epidemiological and dynamic changes - Awatef Taktak; Saba Gargouri; Amel Chtourou; Fahmi Smaoui; Rim Karray; Noureddine Rekik; Lamia Feki-Berrajah; Héla Karray-Hakim (Elsevier, 2024)
Background: Changing patterns in community respiratory virus activity were reported in different geographical locations during the COVID-19 pandemic. In this study, we aimed to assess the prevalence of circulating respiratory viruses, including SARS-CoV-2, during the season 2021-2022 in Tunisia. Methods: We retrospectively enrolled 328 nasopharyngeal samples received at the Triage Center of Habib Bourguiba Hospital from patients with acute respiratory symptoms during September 2021-May 2022. All samples were screened for both SARS-CoV-2 and common respiratory viruses. This latter detection was performed using end-point multiplex RT-PCRs, Real-Time PCR, and AllplexTM Respiratory Panel 1 kit (Seegene) for Influenza Virus A (IFVA) and Respiratory Syncytial Virus (RSV) subtyping. Results: Among included patients, at least one viral pathogen was identified in 118 (35.9 %) patients. The detection rate of SARS-CoV-2 was 21.6 %. A low viral coinfection rate was observed (3.3 %). The most prevalent pathogen among non-SARS-CoV-2 viruses was Enterovirus/Rhinovirus (HEV/HRV) (59.6 %) followed by IFVA (15.3 %) and Adenoviruses (ADV) (11.5 %). Only IFVA H3N2 was found to circulate during the study period. A negative virus interaction was eventually induced by SARS-CoV-2, as it was shown by lower levels of activity of non-SARS-CoV-2 viruses (not exceeding 17.7 %) while infections due to pandemic Omicron variants of concern became widespread. Conclusions: This study highlights the relative return of community IFVA circulation during the 2021-2022 season in Tunisia. A negative viral interaction between SARS-CoV-2 and other respiratory viruses is highly suggested, which explains, in addition to the easing of COVID-19 restriction measures, the epidemiological changes in non-SARS-CoV-2 viruses circulation.